The Pressure of Smash Training Using the Drill Method for Male Athletes' Volleyball Smash Skills - Nur, Muhammad; Gunawan, Moh. Rizky; Hudain, Muh. Adnan; Yasriuddin, Yasriuddin; Fahrizal, Fahrizal (ETDC: Indonesian Journal of Research and Educational Review, 2024)
The objective of this research was to determine the effect of smash drill training on smash skills in PT CAS Makassar male athletes. The type of research used is experimental. We selected the research object through total sampling, and the sample comprised 10 individuals. Meanwhile, we processed the data using SPSS 25, which included descriptive analysis, normality tests, and independent sample t-tests. The research results revealed that the smash skills of male athletes in the PT CAS Makassar study highlight the effectiveness of smash drill training. Of smash drill The hypothesis test results, utilizing the independent sample t-test, confirm this; they yield a value of Tcount > Ttable, specifically 10.04 > 2.101. > 2.101. In addition, the average initial ability of 22.80 to 28.40 demonstrates the impact of smash drill training. The increase in the average ability of these athletes indicates that smash drill training enhances the smash skills of PT CAS Makassarmale athletes.